What is the role of corporations in Human Resource Development in a post conflict environment? ArcelorMittal Liberia a case study - Akande, Michelle (2008)
Until recent downturns in the markets, the commodities markets were said to be at the beginning of the 'super cycle' propelled mostly by infrastructural development in countries like China, increased wealth and globalisation. This supercycle coincides with the diminishing of 'low hanging fruit' that is easily accessible high grade metals and minerals. In the search for natural resources, companies have to move into new territories. The post conflict environment is one of them. These environments are usually characterised by amongst other things a low skill base. This paper is concerned with what role the firm has to play in human resource development in post conflict environments. Much literature has been written about human resource development and its applications in the western hemisphere. Literature however on the role on HRD in Africa and more specifically post conflict environments is scant. As changes in governance make the firm a more central actor in sustainable development and more generally the public arena, this research aims to locate the firm within dialogue about human resource development in the post conflict environment. It should be noted that this study references Africa as the case study is based in Liberia. The research objectives were as follows: - Firstly, to explore the dimensions of HRD and CSR. - Secondly, to build a relationship between HRD and Corporate Social Responsibility. - Thirdly, to locate this relationship with the post-conflict context. - And finally, to define the role of the corporation in developing HRD within the post-conflict context, as well as assessing the benefits of doing so. The research adopted a qualitative approach and used a single case study. Research techniques deployed include interviews and document analysis. As a single case study was used, the generalisability of the research is limited. However, findings from the research revealed that although companies may be aware of expectations within this environment, the ability to meet these expectations can be hampered by the culture within the organisation, lack of resources, lack of infrastructure and time pressures to deliver the project at a low cost base. There is still a need for copious research in this area, however, this study surfaces the important role of responsible human resource development, in both the capacity building of resources within the firm and in society.